Bouquetins et Pyrénées I - De la Préhistoire à nos jours : offert à Jean Clottes, conservateur général du Patrimoine honoraire - Averbouh, Aline; Feruglio, Valérie; Plassard, Frédéric; Sauvet, Georges (Préhistoires de la Méditerranée, 2021)
Emblematic animal of the Pyrenees, the Ibex has inhabited its two slopes since the most ancient times. By adapting to this environment, a typical Pyrenean form Capra Pyrenaica appeared several millennia ago. Consumed during Prehistory, the Ibex became, during the Upper Paleolithic, an unavoidable figure of the prehistoric bestiary. Many of its representations are world-famous: painted Ibex from Salon Noir (Niaux cave, Ariège) or sculpted on sperm whale teeth (Mas d'Azil cave, ariège). The adventure of Ibex in the Pyrenees continues to this day. Victim of intensive hunting, the "goat" had disappeared from its northern slope at the beginning of the 20th century. Recent repopulation programs, launched by the Occitan region, have successfully remedied this situation. Bringing together some fifty specialists of various nationalities, this work, accessible to the general public, offers in this first volume a general panorama ranging from the fossil history of the Ibex to current reintroduction programs, including its ethology and its role in prehistoric and medieval iconography. Volume II, devoted solely to prehistoric representations, offers a detailed inventory of them that is largely unpublished and richly illustrated. This work is dedicated to Jean Clottes, prehistorian, Ariegeois, honorary general curator of heritage at the Ministry of Culture and international specialist of decorated caves.